Red Yeast Rice for Hyperlipidemia: A Meta-Analysis of 15 High-Quality Randomized Controlled Trials - Li, Pengfan; Wang, Qi; Chen, Kanjun; Zou, Shihui; Shu, Shi; Lu, Chanchan; Wang, Shiyun; Jiang, Yunqin; Fan, Chunxiang; Luo, Yue (Frontiers in Pharmacology, 2022)
Background: RYR is a commonly used lipid-lowering dietary supplements in Asian and European countries, showing considerable benefits and low toxicity. This quantitative study aims to present high-quality evidence regarding the efficacy and safety of RYR in treating hyperlipidemia, in order to promote its clinical application. Methods: PubMed, Embase, and Cochrane Central Register of Controlled Trials databases were systematically searched, and high-quality randomized controlled trials comparing RYR with non-RYR interventions were included. RevMan5.3 software was used to conduct the meta-analysis. Results: A total of 1,012 individuals participated in this study (481 in the experimental and 531 in the control group). In comparison to statins, RYR was more effective in lowering TG (MD, -19.90; 95% CI, -32.22 to -7.58; p=0.002), comparable in lowering LDL-C and elevating HDL-C, and less effective in lowering TC (MD, 12.24; 95% CI, 2.19 to 22.29; p=0.02). Compared with nutraceutical, RYR significantly reduced TC (MD, -17.80; 95% CI, -27.12 to -8.48; p=0.0002) and LDL-C (MD, -14.40; 95% CI, -22.71 to -6.09; p=0.0007), and elevated HDL-C (MD, 7.60; 95% CI, 4.33 to 10.87; p<0.00001). Moreover, RYR effectively synergized nutraceutical to further reduce TC (MD, -31.10; 95% CI, -38.83 to -23.36; p<0.00001), LDL-C (MD, -27.91; 95% CI, -36.58 to -19.24; p<0.00001), and TG (MD, -26.32; 95% CI, -34.05 to -18.59; p<0.00001). Additionally, RYR significantly reduced apoB (MD, -27.98; 95% CI, -35.51 to -20.45; p<0.00001) and, whether alone or in combination, did not increase the risk of adverse events in patients with hyperlipidemia. Conclusion: RYR at 200mg to 4800mg daily appears to be a safe and effective treatment for hyperlipidemia, effectively regulating blood lipid levels with an exceptional impact on TG. Looking forward, high-quality clinical trials with longer observation periods are required to evaluate the efficacy and safety of RYR as a long-term medication.